2015
DOI: 10.1111/dote.12377
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative carboplatin and paclitaxel-based chemoradiotherapy for esophageal carcinoma: results of a modified CROSS regimen utilizing radiation doses greater than 41.4 Gy

Abstract: Trimodality therapy for resectable esophageal and gastroesophageal junction cancers utilizing preoperative radiotherapy with concurrent carboplatin and paclitaxel-based chemotherapy is being increasingly utilized secondary to the results of the phase III CROSS trial. However, there is a paucity of reports of this regimen as a component of chemoradiotherapy in North America. We aim to report on our clinical experience using a modified CROSS regimen with higher radiotherapy doses. Patients with advanced (cT2-cT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
5
16
3
Order By: Relevance
“…However, if these values are ascribed to surgery, it is possible that patients in the HD (having higher T stage and node positive disease) required more extensive surgeries and hence a greater likelihood of complications. This is consistent with a retrospective single-institution report of HD therapy being associated with more acute adverse effects and potentially suboptimal surgical conditions (23). Nevertheless, in light of studies demonstrating that advanced RT techniques may decrease adverse and postoperative events, further work must assess whether a decrease in dose has additive effects as well (24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 84%
“…However, if these values are ascribed to surgery, it is possible that patients in the HD (having higher T stage and node positive disease) required more extensive surgeries and hence a greater likelihood of complications. This is consistent with a retrospective single-institution report of HD therapy being associated with more acute adverse effects and potentially suboptimal surgical conditions (23). Nevertheless, in light of studies demonstrating that advanced RT techniques may decrease adverse and postoperative events, further work must assess whether a decrease in dose has additive effects as well (24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 84%
“…The dosage used in this study (46 Gy) was comparable with the dose used in the NEOSCOPE phase II trial (45 Gy) [18]. Interestingly, contrary to other reports, we did not observe increased morbidity using a higher dosage of radiation [19]. This may be explained by a considerable difference in dosage of radiation (50.4 Gy vs. 46 Gy in this publication) [19].…”
Section: Discussionsupporting
confidence: 41%
“…Finally, the higher doses of radiation used at our institution (50.4 Gy) compared to the published CROSS regimen of (41.4 Gy) may also contribute to increased toxicity and decreased survival. 17 It is worth mentioning that the tolerability profile of carboplatin/paclitaxel is generally considered to be superior to that of cisplatin/5-fluorouracil in terms of side effects and patient experience. While direct dosing and tolerability data could not be expressly collected in this study due to the disparate locations across a wide geographical area where our patients received their chemotherapy, other authors have demonstrated this to be the case.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advancements, esophageal cancer remains a prevalent and deadly malignancy with an urgent need for further refined treatment strategies. Future studies evaluating the efficacy of various neoadjuvant approaches, such as the currently enrolling PROTECT trial, 16 as well as evaluation of different radiation doses and modalities 17 will be an integral part of improving outcomes of this highly morbid disease. Such research is vital to further elucidate the role of alternate neoadjuvant chemotherapy regimens in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%